The effects of instructional scaffolding in students conceptual understanding, proving skills, attitudes and perceptions towards direct proofs of integers - Dy, Audric Curtis Pe (Animo Repository, 2018)
The study focused on attitude, perceptions, proving skills and conceptual understanding of students in direct proofs involving integers. The teaching strategy used was instructional scaffolding. The purpose of the study is to determine if there is a development towards attitudes, perceptions, proving skills and conceptual understanding of the students after the interventions involving instructional scaffolding. There were 26 Grade 11 STEM participants. They were provided surveys involving attitudes and perceptions on proof before and after the interventions, where instructional scaffolding took place. The research designs used were both qualitative and quantitative. The attitudes and perceptions were measured through survey means and computed through SPSS. The significance probability was used to determine the significant difference between attitudes before and after interventions as well as perceptions. Based on the findings, the attitudes and perceptions of the students had improved through higher means. There was a significant difference between attitudes and perceptions respectively before and after the interventions. The students were able to develop their proving skills through the series of interventions although half of the participants had retained their levels. The criteria for grading the students understanding towards proof were: 1.) logical correctness, 2.) opening, 3.) stating the conclusion and 4.) organization. The misconceptions gathered during the interventions and tests were improper representations of the integers and computations regarding the polynomials.